杜甫府試下策試説
<span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":641,"3":"1":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">LANGUAGE NOTE | Document text in Chinese; abstract also in English. <span data-sheets-value=""1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English."" data-sheets-userformat=""2":641,"3":"1":0,"10":1,"12":0" data-sheets-validation-definition=""1":"1":"1":24,"2":["1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":0,"5":"1":"1":0,"2":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ],"2":"1":"1":["1":4,"6":0,"1":2,"3":"TRIM","4":1,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese; abstract also in English." ,"1":3,"5":"1":2,"2":"LANGUAGE NOTE | Document text in Chinese only." ,"1":2,"3":"ARRAY_ROW","4":2,"1":2,"3":"ARRAY_LITERAL","4":1,"1":2,"3":"TRIM","4":1,"1":2,"3":"EXACT","4":2,"1":2,"3":"OR","4":1,"1":2,"3":"ARRAYFORMULA","4":1,"1":1,"2":"="],"3":"R0]FTRIM:1]LSLANGUAGE NOTE | Document text in Chinese; abstract also in English.]]LSLANGUAGE NOTE | Document text in Chinese only.]]FARRAY_ROW:2]FARRAY_LITERAL:1]FTRIM:1]FEXACT:2]FOR:1]FARRAYFORMULA:1]S","3":["1":"1":0,"2":1,"3":0,"4":1,"5":1118464,"2":0],"2":"","3":0,"4":1" data-sheets-validation-id="0">自宋至今，各種提到杜甫生平的文字，大抵都認為杜甫在二十三歲到二十六歲，即唐玄宗開元二十二年（734）至二十五年（737）之間曾經獲得解送而參加吏部由考功員外郎主持的進士試，結果落第；唐代進士試分三個階段進行：縣試、州、府試和初由吏部繼由禮部負責的中央級試；杜甫是在第三階段的考試中失敗的。譬如各種前人年譜之中，有的説“赴京兆薦貢，考功下之；”有的説“赴京兆貢舉，不第；”固然明指第三階段。就是有的把“赴鄉舉”和“下第”兩事隔年列出，指的還是第三階段：那是説鄉舉成功以後，再赴京兆考試而失敗。各種年譜、傳記、序文作者的結論應該是根據杜甫的《壯遊》詩自述而來，不過如果抱着上述的結論回轉頭讀《壯遊》詩，其中又不免頗有難解之處。換句話説，重新考慮之下，能不能據《壯遊》詩得出上述的結論，仍可商榷。然而杜甫中央級考試落敗是古今大多數人承認的事實，不宜輕率否定。下文提出的疑慮，只能看成個人讀書之後的反應，作為問題提出來供時賢參考，未敢有即時推翻取代成説之意。(撮要取自內文首段) There were two levels in the T’ang examination system: the local one and the national one. It is believed traditionally that Tu Fu failed the national examination. The author of this paper argued that from evidence gathered, Tu Fu had failed the local test, and never took the national test. (Abstract taken from first paragraph of document.) , journal=人文中國學報, author=鄺健行, year=1995, month=Apr., pages=161–172